Crystalline forms of a cdk inhibitor and pharmaceutically acceptable salts thereof and uses thereof
Patent Information
- Application Number
- CN202480000053.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-17
- Filing Date
- 2024-01-16
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-01-16
AI Technical Summary
然而,该化合物及其可药用盐的晶型尚未进行系统的研究
Smart Images

Figure CN118679171B_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims priority and benefit to Chinese Patent Application No. 202310199886.6, filed with the China National Intellectual Property Administration on January 17, 2023, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] This application belongs to the pharmaceutical field, specifically relating to a CDK inhibitor and its pharmaceutically acceptable salt crystal form and its uses. Background Technology
[0004] In recent years, cancer has surpassed cardiovascular disease to become the leading cause of death worldwide, making anti-tumor drug research of significant academic and practical importance. Overactivation and persistent cell proliferation are fundamental characteristics of tumors; therefore, inducing cell cycle arrest can effectively inhibit tumor growth. Cyclin-dependent kinases (CDKs) belong to the serine / threonine protein kinase family and are key kinases involved in cell cycle regulation. Currently, 20 different CDKs have been reported, which can be mainly divided into two categories based on their functions. One category of CDKs participates in cell cycle regulation, mainly including CDK1, CDK2, CDK4, and CDK6. The other category of CDKs participates in transcriptional regulation, mainly including CDK7, CDK8, CDK9, CDK10, and CDK11. In tumor cells, overexpression or overactivation of cyclins, inhibition of CDKi activity, and persistent activation of upstream mitotic signals can all cause changes in CDK activity. Dysregulation of CDK activity can directly or indirectly lead to uncontrolled cell proliferation, genomic instability (increased DNA mutations, chromosome deletions, etc.), and chromosomal instability (changes in chromosome number), thus participating in tumorigenesis and development. Since CDK activity is essential for cell division, and is often enhanced in tumor cells, CDKs have long been considered promising targets for drug development targeting anti-tumor and other proliferative disorders.
[0005] Currently, the clinical application of multiple CDK4 / 6 inhibitors has fully validated the effectiveness of this target. For example, Pfizer's palbociclib, Eli Lilly's abemaciclib, Novartis' ribociclib, and Hengrui Medicine's dalpiciclib are all used to treat advanced or metastatic breast cancer that is hormone receptor positive (HR+) and human epidermal growth factor receptor 2 negative (HER2-).
[0006] For patients with HR+ / HER2- advanced or metastatic breast cancer, early treatment often involves endocrine therapy. Commonly used endocrine therapy drugs include anastrozole, letrozole, exemestane, tamoxifen, toremifene, fulvestrant, medroxyprogesterone acetate, fluorometholone, and ethinylestradiol. Early-stage intermediate- or high-risk patients can receive chemotherapy concurrently. For advanced or metastatic patients, the current first-line standard treatment is a combination of CDK4 / 6 inhibitors and endocrine therapy. Several authoritative guidelines, both domestic and international, including the Breast Cancer Diagnosis and Treatment Guidelines (2022 edition) issued by the National Health Commission of China, the CSCO Breast Cancer Diagnosis and Treatment Guidelines (2022 edition), and the NCCN Breast Cancer Clinical Practice Guidelines (2022 edition), have raised the evidence level for CDK4 / 6 inhibitors combined with endocrine therapy to Level I, recommending their clinical application in HR+ / HER2- advanced breast cancer.
[0007] WO2021139817A1 discloses a CDK inhibitor compound A, the structure of which is shown in formula (I):
[0008]
[0009] In vitro studies have shown that this compound exhibits strong inhibitory activity against various CDK and TRK kinases, as well as good in vivo bioavailability, making it a promising candidate for treating various related diseases, including cancer. However, a systematic study of this compound and its pharmaceutically acceptable salt crystal forms has not yet been conducted. Summary of the Invention
[0010] In a first aspect, this application provides compound A in crystalline form or a pharmaceutically acceptable salt thereof, the structure of compound A being shown in formula (I) below:
[0011]
[0012] In some embodiments, the DSC spectrum of the crystalline form of compound A has an endothermic peak at 256±3℃.
[0013] In some embodiments, this application provides compound A in crystalline form. In some embodiments, said crystalline form of compound A is anhydrous.
[0014] In some embodiments, the crystalline form of compound A is crystal form A-Ⅰ, and the X-ray powder diffraction pattern expressed in 2θ angles (°) using Cu-Kα radiation has characteristic peaks at 5.2±0.2°, 11.4±0.2°, 15.7±0.2°, 20.2±0.2°, and 22.0±0.2°.
[0015] In some embodiments, the crystalline form of compound A is crystal form A-Ⅰ, and the X-ray powder diffraction pattern expressed in 2θ angles (°) using Cu-Kα radiation has characteristic peaks at 5.2±0.2°, 9.5±0.2°, 11.4±0.2°, 15.7±0.2°, 16.3±0.2°, 20.2±0.2°, and 22.0±0.2°.
[0016] In some embodiments, the crystalline form of compound A is crystal form A-Ⅰ, and the X-ray powder diffraction pattern expressed in 2θ angles (°) using Cu-Kα radiation has characteristic peaks at 5.2±0.2°, 9.5±0.2°, 10.4±0.2°, 11.4±0.2°, 12.8±0.2°, 14.1±0.2°, 15.7±0.2°, 16.3±0.2°, 18.6±0.2°, 20.2±0.2°, 22.0±0.2°, and 25.8±0.2°.
[0017] In some embodiments, the crystalline form of compound A is crystal form A-Ⅰ. The peak positions and relative peak intensities in the X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation, are shown in Table 1 below:
[0018] Table 1. X-ray powder diffraction pattern data of crystalline form AI
[0019] 1 5.24 62.6 2 9.62 12.5 3 10.44 11.7 4 11.46 27.1 5 12.89 14.1 6 14.19 10 7 15.77 39.1 8 16.36 34.1 9 18.69 14.6 10 20.28 100 11 20.63 91.3 12 22.07 47.2 13 25.89 25.6
[0020] In some embodiments, the crystalline form of compound A is crystal form A-I, and the X-ray powder diffraction pattern obtained using Cu-Kα radiation is essentially as follows: Figure 1-1 As shown.
[0021] In some embodiments, the crystalline form of compound A is crystal form A-I, and the DSC spectrum of crystal form AI has an endothermic peak at 256±3℃.
[0022] In some embodiments, the crystalline form of compound A is crystal form A-I, and the DSC spectrum of crystal form AI is substantially as follows: Figure 1-3 As shown.
[0023] In some embodiments, the crystalline form of compound A is crystal form A-II, and the X-ray powder diffraction pattern expressed in 2θ angles (°) using Cu-Kα radiation has characteristic peaks at 4.1±0.2°, 16.2±0.2°, 16.8±0.2°, 20.1±0.2°, and 20.7±0.2°.
[0024] In some embodiments, the crystalline form of compound A is crystal form A-II, and the X-ray powder diffraction pattern expressed in 2θ angles (°) using Cu-Kα radiation has characteristic peaks at 4.1±0.2°, 16.2±0.2°, 16.8±0.2°, 17.7±0.2°, 20.1±0.2°, and 20.7±0.2°.
[0025] In some embodiments, the crystalline form of compound A is crystal form A-II. The peak positions and relative peak intensities in the X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation, are shown in Table 2 below:
[0026] Table 2 X-ray powder diffraction pattern data of crystal form A-II
[0027]
[0028]
[0029] In some embodiments, the crystalline form of compound A is crystal form A-II, and the X-ray powder diffraction pattern obtained using Cu-Kα radiation is essentially as follows: Figure 2-1 As shown.
[0030] In some embodiments, the crystalline form of compound A is crystal form A-II, and crystal form A-II is a solvate. In some embodiments, crystal form A-II is a trifluoroethanol solvate of crystalline compound A. In some embodiments, crystal form A-II is a trifluoroethanol solvate of crystalline compound A, wherein the molar ratio of compound A to trifluoroethanol is 1:1.
[0031] In some embodiments, the crystalline form of compound A is crystal form A-II, and the DSC spectrum of crystal form A-II has endothermic peaks at 100-130℃ and 256±3℃.
[0032] In some embodiments, the crystalline form of compound A is crystal form A-II, and the DSC spectrum of crystal form A-II is substantially as follows: Figure 2-3 As shown.
[0033] In some embodiments, the crystalline form of compound A is crystal form A-Ⅲ, and the X-ray powder diffraction pattern expressed in 2θ angles (°) using Cu-Kα radiation has characteristic peaks at 6.6±0.2°, 13.2±0.2°, 16.5±0.2°, 20.1±0.2°, and 23.0±0.2°.
[0034] In some embodiments, the crystalline form of compound A is crystal form A-Ⅲ, and the X-ray powder diffraction pattern expressed in 2θ angles (°) using Cu-Kα radiation has characteristic peaks at 6.6±0.2°, 13.2±0.2°, 15.2±0.2°, 16.5±0.2°, 20.1±0.2°, 23.0±0.2°, and 28.2±0.2°.
[0035] In some embodiments, the crystalline form of compound A is crystal form A-III. The peak positions and relative peak intensities in the X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation are shown in Table 3 below:
[0036] Table 3. X-ray powder diffraction pattern data of crystal form A-III
[0037] 1 6.58 49.9 2 13.19 27 3 15.2 13.3 4 16.53 28.8 5 20.08 100 6 23.01 30.8 7 28.17 11.9
[0038] In some embodiments, the crystalline form of compound A is crystal form A-III, and the X-ray powder diffraction pattern obtained using Cu-Kα radiation is essentially as follows: Figure 3-1 As shown.
[0039] In some embodiments, the crystalline form of compound A is crystal form A-III, and crystal form A-III is a solvate. In some embodiments, crystal form A-III is a dimethyl sulfoxide solvate of crystalline compound A. In some embodiments, crystal form A-III is a dimethyl sulfoxide solvate of crystalline compound A, wherein the molar ratio of compound A to dimethyl sulfoxide is 1:1.
[0040] In some embodiments, the crystalline form of compound A is crystal form A-III, and the DSC spectrum of crystal form A-III has endothermic peaks at 100-150℃ and 256±3℃.
[0041] In some embodiments, the crystalline form of compound A is crystal form A-III, and the DSC spectrum of crystal form A-III is substantially as follows: Figure 3-3 As shown.
[0042] In some embodiments, the crystalline form of compound A is crystal form A-Ⅳ, and the X-ray powder diffraction pattern expressed in 2θ angles (°) using Cu-Kα radiation has characteristic peaks at 4.1±0.2°, 5.4±0.2°, 9.5±0.2°, 12.1±0.2°, 15.9±0.2°, and 20.7±0.2°.
[0043] In some embodiments, the crystalline form of compound A is crystal form A-Ⅳ, and the X-ray powder diffraction pattern expressed in 2θ angles (°) using Cu-Kα radiation has characteristic peaks at 4.1±0.2°, 5.4±0.2°, 9.5±0.2°, 12.1±0.2°, 15.9±0.2°, 17.8±0.2°, 19.3±0.2°, and 20.7±0.2°.
[0044] In some embodiments, the crystalline form of compound A is crystal form A-IV. The peak positions and relative peak intensities in the X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation are shown in Table 4 below:
[0045] Table 4. X-ray powder diffraction pattern data of crystal form A-IV
[0046] 1 4.1 11.4 2 5.36 43.4 3 9.52 20.4 4 12.08 20.1 5 15.9 40.7 6 17.8 19.3 7 19.26 8.4 8 19.87 17.8 9 20.44 100 10 20.72 89.1
[0047] In some embodiments, the crystalline form of compound A is crystal form A-Ⅳ, and the X-ray powder diffraction pattern obtained using Cu-Kα radiation is essentially as follows: Figure 4-1 As shown. In some embodiments, the crystalline form of compound A is crystal form A-IV, and the DSC spectra of crystal form A-IV are substantially as shown. Figure 4-3 As shown.
[0048] In some embodiments, the pharmaceutically acceptable salt of compound A in crystalline form is selected from sulfates, methanesulfonates, tartrates, benzenesulfonates, hydrochlorides, p-toluenesulfonates, fumarates, citrates, and malates; preferably benzenesulfonates, hydrochlorides, p-toluenesulfonates, fumarates, citrates, and malates; more preferably hydrochlorides and benzenesulfonates.
[0049] In some embodiments, the pharmaceutically acceptable salt of compound A in crystalline form is selected from hydrochloride. In some embodiments, the hydrochloride of compound A in crystalline form is a hydrate. In some embodiments, the hydrochloride of compound A in crystalline form is a monohydrate of compound A hydrochloride.
[0050] In some embodiments, the crystalline form of compound A hydrochloride is crystal form B, and its X-ray powder diffraction pattern, expressed in 2θ angles (°) using Cu-Kα radiation, has characteristic peaks at 4.1±0.2°, 8.9±0.2°, 14.3±0.2°, and 19.9±0.2°.
[0051] In some embodiments, the crystalline form of compound A hydrochloride is crystal form B, and its X-ray powder diffraction pattern, expressed in 2θ angles (°) using Cu-Kα radiation, has characteristic peaks at 4.1±0.2°, 8.9±0.2°, 12.3±0.2°, 14.3±0.2°, 15.4±0.2°, 16.8±0.2°, and 19.9±0.2°.
[0052] In some embodiments, the crystalline form of compound A hydrochloride is crystal form B, and its X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation, exhibits characteristic peaks at 4.1±0.2°, 8.3±0.2°, 8.9±0.2°, 9.5±0.2°, 12.3±0.2°, 14.3±0.2°, 15.0±0.2°, 15.4±0.2°, 16.8±0.2°, 19.1±0.2°, 19.9±0.2°, 20.6±0.2°, and 25.5±0.2°.
[0053] In some embodiments, the crystalline form of compound A hydrochloride is crystal form B, and its X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation, exhibits characteristic peaks at 4.1±0.2°, 8.3±0.2°, 8.9±0.2°, 9.5±0.2°, 11.1±0.2°, 12.3±0.2°, 14.3±0.2°, 15.0±0.2°, 15.4±0.2°, 16.8±0.2°, 17.4±0.2°, 19.1±0.2°, 19.9±0.2°, 20.6±0.2°, 21.6±0.2°, 25.2±0.2°, 25.5±0.2°, 26.6±0.2°, and 29.1±0.2°.
[0054] In some embodiments, the crystalline form of compound A hydrochloride is crystal form B. The peak positions and relative peak intensities in the X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation are shown in Table 5 below:
[0055] Table 5. X-ray powder diffraction pattern data of crystal form B.
[0056]
[0057] In some embodiments, the crystalline form of compound A hydrochloride is crystal form B, and the X-ray powder diffraction pattern obtained using Cu-Kα radiation is essentially as follows: Figure 5-1 As shown.
[0058] In some embodiments, the crystalline form of compound A hydrochloride is crystal form B, and its TGA spectrum shows a weight loss of approximately 4.4% in the range of room temperature to 130°C.
[0059] In some embodiments, the crystalline form of compound A hydrochloride is crystal form B, and its DSC spectrum shows an endothermic peak at 253±3℃; in some embodiments, the crystalline form of compound A hydrochloride is crystal form B, and its DSC spectrum shows two endothermic peaks at 27±3℃ and 253±3℃.
[0060] In some embodiments, the crystal form B is a crystalline form of compound A hydrochloride monohydrate, wherein the molar ratio of compound A, hydrochloric acid, and water is 1:1:1.
[0061] In some embodiments, the pharmaceutically acceptable salt of compound A in crystalline form is selected from benzenesulfonate. In some embodiments, the crystalline form of compound A benzenesulfonate is anhydrous. In some embodiments, the molar ratio of free base of compound A to benzenesulfonic acid in the crystalline form of compound A benzenesulfonate is 1:1.
[0062] In some embodiments, the crystalline form of compound A benzenesulfonate is crystal form C, and its X-ray powder diffraction pattern, expressed in 2θ angles (°) using Cu-Kα radiation, has characteristic peaks at 8.5±0.2°, 15.3±0.2°, 19.2±0.2°, 21.7±0.2°, 22.1±0.2°, and 26.1±0.2°.
[0063] In some embodiments, the crystalline form of compound A benzenesulfonate is crystal form C, and its X-ray powder diffraction pattern, expressed in 2θ angles (°) using Cu-Kα radiation, exhibits characteristic peaks at 8.5±0.2°, 15.3±0.2°, 16.4±0.2°, 17.1±0.2°, 17.8±0.2°, 19.2±0.2°, 21.7±0.2°, 22.1±0.2°, and 26.1±0.2°.
[0064] In some embodiments, the crystalline form of compound A benzenesulfonate is crystal form C, and its X-ray powder diffraction pattern, expressed in 2θ angles (°) using Cu-Kα radiation, exhibits characteristic peaks at 8.5±0.2°, 15.3±0.2°, 16.4±0.2°, 17.1±0.2°, 17.8±0.2°, 18.1±0.2°, 19.2±0.2°, 20.2±0.2°, 21.7±0.2°, 22.1±0.2°, and 26.1±0.2°.
[0065] In some embodiments, the crystalline form of compound A benzenesulfonate is crystal form C, and its X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation, exhibits characteristic peaks at 8.5±0.2°, 11.7±0.2°, 12.7±0.2°, 13.3±0.2°, 14.2±0.2°, 15.3±0.2°, 16.4±0.2°, 17.1±0.2°, 17.8±0.2°, 18.1±0.2°, 19.2±0.2°, 19.5±0.2°, 20.2±0.2°, 21.7±0.2°, 22.1±0.2°, and 26.1±0.2°.
[0066] In some embodiments, the crystalline form of compound A benzenesulfonate is crystal form C. The peak positions and relative peak intensities in the X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation are shown in Table 6 below:
[0067] Table 6. X-ray powder diffraction pattern data of crystal form C
[0068]
[0069] In some embodiments, the crystalline form of compound A benzenesulfonate is crystal form C, and X-ray powder diffraction is substantially as follows using Cu-Kα radiation. Figure 6-1 As shown.
[0070] In some embodiments, the crystalline form of compound A benzenesulfonate is crystal form C, and its DSC spectrum shows an endothermic peak at 235±3℃.
[0071] In some embodiments, the crystalline form of compound A benzenesulfonate is crystal form C, and the DSC spectrum is essentially as follows: Figure 6-2 As shown.
[0072] In some embodiments, the crystal form C is a crystalline form of compound A benzenesulfonate, wherein the molar ratio of compound A to benzenesulfonic acid is 1:1.
[0073] In some embodiments, the pharmaceutically acceptable salt of compound A in crystalline form is selected from p-toluenesulfonate. In some embodiments, the p-toluenesulfonate of compound A in crystalline form is a hydrate.
[0074] In some embodiments, the crystalline form of compound A p-toluenesulfonate is crystal form D-I, and its X-ray powder diffraction pattern, expressed in 2θ angles (°) using Cu-Kα radiation, has characteristic peaks at 9.1±0.2°, 13.3±0.2°, 15.8±0.2°, 19.6±0.2°, and 20.9±0.2°.
[0075] In some embodiments, the crystalline form of compound A p-toluenesulfonate is crystal form D-I, and its X-ray powder diffraction pattern, expressed in 2θ angles (°) using Cu-Kα radiation, exhibits characteristic peaks at 7.9±0.2°, 9.1±0.2°, 12.9±0.2°, 13.3±0.2°, 15.8±0.2°, 18.5±0.2°, 19.6±0.2°, and 20.9±0.2°.
[0076] In some embodiments, the crystalline form of compound A p-toluenesulfonate is crystal form D-I. The peak positions and relative peak intensities in the X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation, are shown in Table 7 below:
[0077] Table 7 X-ray powder diffraction pattern data of crystal form D-I
[0078] 1 7.866 20.60% 2 9.126 100.00% 3 12.982 26.70% 4 13.299 33.00% 5 15.817 29.10% 6 18.538 34.60% 7 19.565 35.30% 8 20.942 87.80%
[0079] In some embodiments, the crystalline form of compound A p-toluenesulfonate is crystal form D-I, and X-ray powder diffraction is substantially as follows using Cu-Kα radiation. Figure 7-1 As shown.
[0080] In some embodiments, the crystalline form of compound A p-toluenesulfonate is crystal form D-I, and TGA exhibits approximately 4.2% weight loss in the range of room temperature to 150°C.
[0081] In some embodiments, the crystalline form of compound A p-toluenesulfonate is crystal form D-I, and its DSC spectrum shows a broad endothermic peak at 167±3℃; in some embodiments, the crystalline form of compound A p-toluenesulfonate is crystal form DI, and its DSC spectrum shows two broad endothermic peaks at 49±3℃ and 167±3℃.
[0082] In some embodiments, the crystalline form of compound A p-toluenesulfonate is crystal form D-I, and its DSC spectrum is essentially as follows: Figure 7-2 As shown.
[0083] In some embodiments, the crystal form DI is a crystalline form of compound A p-toluenesulfonate monohydrate, wherein the molar ratio of compound A, p-toluenesulfonic acid, and water is 1:1:1.
[0084] In some embodiments, the pharmaceutically acceptable salt of compound A in crystalline form is selected from fumarate. In some embodiments, the molar ratio of fumaric acid to the free base of compound A in the crystalline form of fumarate is 1:1. In some embodiments, the crystalline form of compound A fumarate is a hydrate. In some embodiments, the crystalline form of compound A fumarate is a monohydrate.
[0085] In some embodiments, the crystalline form of compound A fumarate is crystal form E, and its X-ray powder diffraction pattern, expressed in 2θ angles (°) using Cu-Kα radiation, has characteristic peaks at 4.1±0.2°, 13.2±0.2°, 16.6±0.2°, 19.9±0.2°, and 21.5±0.2°.
[0086] In some embodiments, the crystalline form of compound A fumarate is crystal form E, and its X-ray powder diffraction pattern, expressed in 2θ angles (°) using Cu-Kα radiation, exhibits characteristic peaks at 4.1±0.2°, 8.4±0.2°, 12.5±0.2°, 13.2±0.2°, 13.9±0.2°, 16.6±0.2°, 19.9±0.2°, 21.5±0.2°, and 22.1±0.2°.
[0087] In some embodiments, the crystalline form of compound A fumarate is crystal form E. The peak positions and relative peak intensities in the X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation are shown in Table 8 below:
[0088] Table 8. X-ray powder diffraction pattern data of crystal form E
[0089] 1 4.148 100.00% 2 8.35 9.20% 3 12.474 14.70% 4 13.196 20.30% 5 13.917 7.20% 6 16.608 26.30% 7 19.92 34.30% 8 21.488 20.10% 9 22.113 19.30%
[0090] In some embodiments, the crystalline form of compound A fumarate is crystal form E, and X-ray powder diffraction is substantially as follows using Cu-Kα radiation. Figure 9-1 As shown.
[0091] In some embodiments, the crystalline form of compound A fumarate is crystal form E, and its DSC spectrum shows endothermic peaks at 222±3℃, 230±3℃, and 240±3℃. In some embodiments, the crystalline form of compound A fumarate is crystal form E, and its DSC spectrum shows an exothermic peak at 159±3℃ and endothermic peaks at 32±3℃, 222±3℃, 230±3℃, and 240±3℃.
[0092] In some embodiments, the crystalline form of compound A fumarate is crystal form E, and the DSC spectrum is essentially as follows: Figure 9-2 As shown.
[0093] In some embodiments, the crystal form E is a crystalline form of compound A fumarate monohydrate, wherein the molar ratio of compound A, fumaric acid and water is 1:1:1.
[0094] In some embodiments, the pharmaceutically acceptable salt of compound A in crystalline form is selected from citrates. In some embodiments, the molar ratio of free base of compound A to citric acid in the citrate of compound A in crystalline form is 1:1. In some embodiments, the citrate of compound A in crystalline form is a hydrate.
[0095] In some embodiments, the crystalline form of compound A citrate is crystal form F, and its X-ray powder diffraction pattern, expressed in 2θ angles (°) using Cu-Kα radiation, has characteristic peaks at 10.1±0.2°, 15.5±0.2°, 17.1±0.2°, 19.4±0.2°, 20.0±0.2°, and 21.5±0.2°.
[0096] In some embodiments, the crystalline form of compound A citrate is crystal form F, and its X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation, exhibits characteristic peaks at 10.1±0.2°, 11.1±0.2°, 12.5±0.2°, 15.5±0.2°, 17.1±0.2°, 18.4±0.2°, 19.4±0.2°, 20.0±0.2°, 21.5±0.2°, 23.0±0.2°, and 24.2±0.2°.
[0097] In some embodiments, the crystalline form of compound A citrate is crystal form F, and the X-ray powder diffraction pattern expressed in 2θ angles using Cu-Kα radiation has characteristic peaks at 10.1±0.2°, 11.1±0.2°, 12.5±0.2°, 13.0±0.2°, 14.1±0.2°, 15.5±0.2°, 16.6±0.2°, 17.1±0.2°, 17.5±0.2°, 18.4±0.2°, 19.4±0.2°, 20.0±0.2°, 20.5±0.2°, 21.5±0.2°, 23.0±0.2°, 24.2±0.2°, and 24.7±0.2°.
[0098] In some embodiments, the crystalline form of compound A citrate is crystal form F. The peak positions and relative peak intensities in the X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation are shown in Table 9 below:
[0099] Table 9. X-ray powder diffraction pattern data of crystal form F.
[0100]
[0101] In some embodiments, the crystalline form of compound A citrate is crystal form F, and X-ray powder diffraction is substantially as follows using Cu-Kα radiation. Figure 10-1 As shown.
[0102] In some embodiments, the crystalline form of compound A citrate is crystal form F, and its DSC spectrum shows three endothermic peaks at 30±3℃, 198±3℃, and 248±3℃.
[0103] In some embodiments, the crystalline form of compound A citrate is crystal form F, and the DSC spectrum is essentially as follows: Figure 10-2 As shown.
[0104] In some embodiments, the crystal form F is a crystalline form of compound A citrate hydrate, wherein the molar ratio of compound A to citric acid is 1:1.
[0105] In some embodiments, the pharmaceutically acceptable salt of compound A in crystalline form is selected from malates. In some embodiments, the molar ratio of malic acid to the free base of compound A in the crystalline form of malate is 1:1. In some embodiments, the crystalline form of compound A malate is a hydrate. In some embodiments, the crystalline form of compound A malate is a monohydrate.
[0106] In some embodiments, the crystalline form of compound A malate is crystal form G, and its X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation, exhibits characteristic peaks at 4.0±0.2°, 11.4±0.2°, 12.4±0.2°, 19.6±0.2°, 20.4±0.2°, 21.1±0.2°, and 22.5±0.2°.
[0107] In some embodiments, the crystalline form of compound A malate is crystal form G, and its X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation, exhibits characteristic peaks at 4.0±0.2°, 9.8±0.2°, 10.5±0.2°, 11.4±0.2°, 12.4±0.2°, 13.2±0.2°, 14.3±0.2°, 15.9±0.2°, 17.0±0.2°, 19.0±0.2°, 19.6±0.2°, 20.4±0.2°, 21.1±0.2°, 22.5±0.2°, 24.1±0.2°, and 25.4±0.2°.
[0108] In some embodiments, the crystalline form of compound A malate is crystal form G. The peak positions and relative peak intensities in the X-ray powder diffraction pattern, expressed in 2θ angles (°), using Cu-Kα radiation are shown in Table 10 below:
[0109] Table 10 X-ray powder diffraction pattern data of crystal form G
[0110]
[0111] In some embodiments, the crystalline form of compound A malate is crystal form G, and X-ray powder diffraction is substantially as follows using Cu-Kα radiation. Figure 11-1 As shown.
[0112] In some embodiments, the crystalline form of compound A malate is crystal form G, and its DSC spectrum shows endothermic peaks at 57±3℃, 175±3℃, 191±3℃, and 238±3℃.
[0113] In some embodiments, the crystalline form of compound A malate is crystal form G, and the DSC spectrum is essentially as follows: Figure 11-2 As shown.
[0114] In some embodiments, the crystal form G is a compound A malate monohydrate, wherein the molar ratio of compound A, malic acid and water is 1:1:1.
[0115] Secondly, this application also provides a pharmaceutical composition comprising compound A in its crystalline form as described above, or a pharmaceutically acceptable salt thereof. In some embodiments, this application provides a pharmaceutical composition comprising one or more of the following crystal forms as described above: crystal form AI, crystal forms A-II, crystal forms A-III, crystal forms A-IV, crystal form B, crystal form C, crystal form DI, crystal form E, crystal form F, and crystal form G, and optionally one or more pharmaceutically acceptable excipients. Preferably, the pharmaceutical composition comprises one or more of the following crystal forms as described above: crystal form AI, crystal form B, and crystal form C, and optionally one or more pharmaceutically acceptable excipients.
[0116] Thirdly, this application also provides the use of compound A in its crystalline form as described above, or a pharmaceutically acceptable salt thereof, in the preparation of an antitumor drug. In some embodiments, this application provides the use of crystal forms AI, A-II, A-III, A-IV, B, C, DI, E, F, G, or pharmaceutical compositions as described above, in the preparation of an antitumor drug.
[0117] Fourthly, this application also provides a method for treating tumors using the crystalline form of compound A or its pharmaceutically acceptable salt as described above, comprising administering a therapeutically effective amount of the crystalline form of compound A or its pharmaceutically acceptable salt to a subject or patient requiring treatment. In some embodiments, this application provides a method for treating tumors comprising administering a therapeutically effective amount of the crystalline form AI, crystalline form A-II, crystalline form A-III, crystalline form A-IV, crystalline form B, crystalline form C, crystalline form DI, crystalline form E, crystalline form F, crystalline form G, or a pharmaceutical composition as described above to a subject or patient requiring treatment.
[0118] Fifthly, this application also provides compound A in the crystalline form described above, or a pharmaceutically acceptable salt thereof, for the treatment of tumors. In some embodiments, this application also provides crystal forms A1, A-II, A-III, A-IV, B, C, D1, E, F, G, or pharmaceutical compositions as described above for the treatment of tumors.
[0119] Sixthly, this application also provides the use of compound A in its crystalline form as described above, or a pharmaceutically acceptable salt thereof, in the treatment of tumors. In some embodiments, this application provides the use of crystal forms A1, A-II, A-III, A-IV, B, C, D1, E, F, G, or pharmaceutical compositions as described above, in the treatment of tumors.
[0120] All of the above aspects:
[0121] In some embodiments, the tumor is selected from sensitive tumors or drug-resistant tumors. Preferably, the sensitive tumor or drug-resistant tumor is selected from solid tumors or hematologic malignancies. Preferably, the solid tumor is selected from fibrosarcoma, salivary gland carcinoma, liver cancer, colorectal cancer, bladder cancer, pharyngeal cancer, breast cancer, prostate cancer, glioma, ovarian cancer, head and neck squamous cell carcinoma, cervical cancer, esophageal cancer, kidney cancer, pancreatic cancer, skin cancer, lymphoma, gastric cancer, multiple myeloma, brain tumor, lung cancer, and melanoma; the hematologic malignancies are selected from acute myeloid leukemia. More preferably, the sensitive tumor or drug-resistant tumor is selected from breast cancer, lung cancer, colorectal cancer, liver cancer, ovarian cancer, melanoma, and acute myeloid leukemia. In some embodiments, the breast cancer is selected from HR+ / HER2- breast cancer, triple-negative breast cancer, and HR- / HER2+ breast cancer; the acute myeloid leukemia is selected from myeloid monocytic leukemia; and the lung cancer is selected from non-small cell lung cancer.
[0122] In some embodiments, the tumor is selected from drug-resistant tumors. The drug-resistant tumor is selected from primary drug-resistant tumors or acquired drug-resistant tumors.
[0123] In some embodiments, the drug-resistant tumor is selected from CDK4 / 6 inhibitor-resistant tumors, and further selected from CDK4 / 6 inhibitor-primarily drug-resistant tumors or CDK4 / 6 inhibitor-acquired drug-resistant tumors. The CDK4 / 6 inhibitor is selected from palbociclib, abemaciclib, ribociclib, and dalpiciclib, with palbociclib being preferred.
[0124] In some embodiments, the CDK4 / 6 inhibitor-resistant tumors are selected from breast cancer and liver cancer, more preferably breast cancer and liver cancer resistant to palbociclib, and even more preferably breast cancer or liver cancer with primary resistance to palbociclib or acquired resistance to palbociclib. The breast cancer with primary resistance to palbociclib or acquired resistance to palbociclib is selected from HR+ / HER2- breast cancer, triple-negative breast cancer, and HR- / HER2+ breast cancer with primary or acquired resistance to palbociclib.
[0125] The crystalline form of compound A or its pharmaceutically acceptable salt described in this application can be administered as a monotherapy or in combination with other clinically / pharmaceuticalally acceptable antitumor drugs, biotherapy, radiotherapy, and / or traditional Chinese medicine treatments. In some embodiments, the other antitumor drugs are selected from endocrine therapy drugs, such as anastrozole, letrozole, exemestane, tamoxifen, toremifene, fulvestrant, medroxyprogesterone acetate, fluorometholone, ethinylestradiol, preferably fulvestrant.
[0126] Accordingly, this application provides the use of compound A in crystalline form or a pharmaceutically acceptable salt thereof in combination with other clinically / pharmaceuticalally acceptable drugs for the preparation of an antitumor drug. Simultaneously, this application provides an antitumor drug comprising compound A in crystalline form or a pharmaceutically acceptable salt thereof, and other clinically / pharmaceuticalally acceptable drugs. The other drugs may be contained in the same formulation unit as compound A in crystalline form or a pharmaceutically acceptable salt thereof, or may be contained in different formulation units, in a combined package form, such as a kit product. In some embodiments, the other drugs are selected from endocrine therapy drugs, such as anastrozole, letrozole, exemestane, tamoxifen, toremifene, fulvestrant, megestrol acetate, fluorometholone, ethinylestradiol, preferably fulvestrant.
[0127] The inventors studied the crystallization state of compound A and its pharmaceutical salt. The results showed that compound A failed to form crystalline salts with maleic acid and phosphoric acid; the salts formed with sulfuric acid, methanesulfonic acid, and tartaric acid had poor crystallinity; it did not react completely with succinic acid; hydrochloride, p-toluenesulfonate, citrate, fumaric acid, and malate were solvent compounds / hydrates; only benzenesulfonate was amorphous. Based on the solid-state characterization results, hydrochloride crystal form B (hydrate) and benzenesulfonate crystal form C (amorphous) were the dominant salt forms.
[0128] Further comparison of the solubility and stability of hydrochloride crystal form B (hydrate), benzenesulfonate crystal form C (amorphous form), and free alkali crystal form A-I revealed that free alkali crystal form A-I has low solubility in water, while the two salt crystal forms have significantly higher solubility. However, in the other three biorelevant media, the solubility of free alkali crystal form A-I and the two salt crystal forms is not significantly different, and the solubility in SGF is greater than 5 mg / mL. Solid stability results showed that benzenesulfonate crystal form C may transform into hydrate under 92.5% RH conditions. Free alkali crystal form A-I, hydrochloride crystal form B, and benzenesulfonate crystal form C all exhibited certain physical and chemical stability after 7 days of storage under three conditions: 60℃, 92.5% RH, and 40℃ / 75% RH.
[0129] Preclinical studies have shown that compound A in crystalline form or its pharmaceutically acceptable salt can significantly inhibit the proliferation of various tumor cells, including breast cancer, colorectal cancer, ovarian cancer, melanoma, liver cancer, lung cancer, and acute myeloid leukemia. It also has a good inhibitory effect on palbociclib-resistant (including primary and acquired resistance) breast cancer and liver cancer.
[0130] Therefore, the crystalline form of compound A or its pharmaceutically acceptable salt has great clinical application prospects for treating advanced malignant tumors and provides a new drug option for treating CDK4 / 6 inhibitor-resistant tumors.
[0131] Definitions and Explanations
[0132] Unless otherwise stated, the following terms and phrases used herein are intended to have the following meanings. A particular phrase or term should not be considered uncertain or unclear unless specifically defined, but should be understood in its ordinary sense.
[0133] The crystalline form of compound A or its pharmaceutically acceptable salt mentioned in this application includes the anhydrous and solvent-free form, hydrate form, solvate form and eutectic form of compound A or its pharmaceutically acceptable salt.
[0134] The term "room temperature" refers to room temperature in the conventional sense of the art, generally 10 to 30°C, preferably 25°C ± 5°C.
[0135] In X-ray powder diffraction (XRD) patterns, the term "substantially" or "substantially as shown" refers to a substantially pure crystal form in which at least 50%, 60%, 70%, 80%, 90%, 95%, 96%, 97%, 98%, or 99% of the peaks appear in the given pattern. Furthermore, as the content of a crystal form in a product gradually decreases, some diffraction peaks attributable to that crystal form in the XRD pattern may decrease due to factors such as the instrument's detection sensitivity. Additionally, for any given crystal form, the peak positions may have slight errors, which is well known in crystallography. For example, peak positions can shift due to variations in temperature during sample analysis, sample movement, or instrument calibration; the measurement error for the 2θ value is sometimes approximately ±0.3°, and typically approximately ±0.2°. Therefore, this error should be taken into account when determining each crystal structure, and the terms "substantially" or "substantially as shown in the figure" are also intended to cover such differences in diffraction peak positions, referring to ±0.3°, preferably ±0.2°.
[0136] In DSC or TGA spectra, the term "substantially" or "substantially as shown" means that for the same crystal form of the same compound, the error in the thermal transition onset temperature, endothermic peak peak temperature, exothermic peak peak temperature, melting point, weight loss onset temperature, or weight loss endpoint temperature, etc., in continuous analysis, is typically ±5℃, usually ±3℃.
[0137] The term "tumor" includes benign tumors, malignant tumors, and borderline tumors, with malignant tumors collectively referred to as cancer.
[0138] As used herein, the term "prevention" means, when used for a disease or condition (e.g., cancer), that the compound or drug reduces the frequency of symptoms of the medical condition or delays the onset of the condition in a subject compared to a subject who has not been given the compound or drug (e.g., the combination product claimed in this application).
[0139] As used in this article, the term “treatment” means to reduce, alleviate or improve the symptoms of a disease or condition, improve underlying metabolic symptoms, suppress a disease or condition, such as preventing the development of a disease or condition, alleviating a disease or condition, causing the remission of a disease or condition, relieving the condition caused by a disease or condition, or preventing the symptoms of a disease or condition.
[0140] The terms "pharmaceuticalally acceptable carrier" or "pharmaceuticalally acceptable excipient" refer to carriers or excipients that do not cause significant irritation to the organism and do not impair the biological activity and properties of the active compound.
[0141] The terms “subject” and “patient” include, but are not limited to, mammals (e.g., mice, rats, cats, monkeys, dogs, horses, pigs) and humans.
[0142] The term "pharmaceutical composition" refers to a mixture of one or more compounds of this application or their salts with pharmaceutically acceptable excipients. The pharmaceutical compositions of this application can be prepared by combining the compounds of this application with suitable pharmaceutically acceptable excipients. The pharmaceutical compositions of this application can be manufactured using methods well known in the art, such as conventional mixing, dissolving, granulation, sugar-coated pill making, grinding, emulsification, freeze-drying, etc.
[0143] For the purposes of pharmaceuticals or pharmacologically active agents, the term "therapeutic effective amount" refers to a sufficient quantity of a drug or agent that is non-toxic but achieves the desired effect. The determination of the effective amount varies from person to person, depending on the recipient's age and general condition, as well as the specific active substance. The appropriate effective amount in a given case can be determined by a person skilled in the art based on routine testing.
[0144] All solvents used in this application are commercially available and can be used without further purification.
[0145] To provide a more concise description, the term "about" is not used for some quantitative data in this document. It should be understood that, whether the term "about" is explicitly used or not, every numerical value given herein includes not only the actual given value (the given value), but also approximations of such a given value based on reasonable inference by one of ordinary skill in the art, including equivalents and approximations of such a given value due to experimental and / or measurement conditions. These approximations are preferably ±20%, ±15%, ±10%, ±8%, ±6%, ±5%, ±4%, ±3%, 2%, or ±1% of the given value. Attached Figure Description
[0146] Figure 1-1 XRPD image of compound A in its free basal form, AI.
[0147] Figure 1-2 TGA image of compound A in its free basal form, AI.
[0148] Figure 1-3 DSC diagram of compound A in its free basal form AI.
[0149] Figure 2-1 XRPD diagram of the free alkali crystal form A-II of compound A.
[0150] Figure 2-2 TGA image of compound A in its free alkali crystal form A-II.
[0151] Figure 2-3DSC diagram of the free alkali crystal form A-II of compound A.
[0152] Figure 3-1 XRPD diagram of the free alkali crystal form A-Ⅲ of compound A.
[0153] Figure 3-2 TGA image of compound A in its free alkali crystal form A-Ⅲ.
[0154] Figure 3-3 DSC diagram of the free alkali crystal form A-Ⅲ of compound A.
[0155] Figure 4-1 XRPD diagram of the free alkali crystal form A-Ⅳ of compound A.
[0156] Figure 4-2 TGA image of compound A in its free alkali crystal form A-Ⅳ.
[0157] Figure 4-3 DSC diagram of free alkali crystal form A-Ⅳ of compound A.
[0158] Figure 5-1 XRPD pattern of compound A hydrochloride crystal form B.
[0159] Figure 5-2 TGA and DSC spectra of compound A hydrochloride crystal form B.
[0160] Figure 6-1 XRPD pattern of compound A benzenesulfonate crystal form C.
[0161] Figure 6-2 TGA and DSC diagrams of benzenesulfonate form C of compound A.
[0162] Figure 7-1 XPRD pattern of compound A p-toluenesulfonate crystal form D-I.
[0163] Figure 7-2 TGA and DSC spectra of compound A p-toluenesulfonate crystal form D-I.
[0164] Figure 8-1 XPRD pattern of compound A p-toluenesulfonate crystal form D-II.
[0165] Figure 8-2 TGA and DSC spectra of compound A p-toluenesulfonate crystal form D-II.
[0166] Figure 9-1 XPRD pattern of fumarate form E of compound A.
[0167] Figure 9-2 TGA and DSC spectra of fumarate E of compound A.
[0168] Figure 10-1 XRPD pattern of citrate form F of compound A.
[0169] Figure 10-2 TGA and DSC spectra of citrate form F of compound A.
[0170] Figure 11-1 XRPD pattern of compound A malate crystal form G.
[0171] Figure 11-2 TGA and DSC spectra of compound A malate crystal form G. Detailed Implementation
[0172] The drugs and reagents involved in the following specific embodiments can all be purchased commercially or prepared using conventional methods in the prior art.
[0173] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as are familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this application. The preferred embodiments and materials shown herein are for illustrative purposes only.
[0174] Detection methods
[0175] 1. X-ray powder diffraction (XRPD)
[0176] Instrument: Bruker D8 Advance Diffractometer
[0177] Detection method: The sample is laid flat on a non-reflective sample plate, and then gently pressed flat before detection. Specific conditions are: Cu-Kα radiation, tube voltage 40kV, tube current 40mA, 2θ scan range 3-40° or 3-30°, scan step size 0.02°, and exposure time 0.2 seconds.
[0178] 2. Differential thermal analysis (DSC)
[0179] Instrument: TA Instruments Q200 DSC
[0180] Detection method: Place 0.5-5 mg of sample in a perforated aluminum dish and heat to the final temperature at a rate of 10℃ / min. The nitrogen purging rate in the furnace is 50 mL / min.
[0181] 3. Thermogravimetric analysis (TGA)
[0182] Instrument: TA Instruments Q500 TGA
[0183] Detection method: Place 1-10 mg of sample in a peeled, open aluminum sample pan and weigh automatically in a TGA heating furnace. The sample is heated to the final temperature at a rate of 10 °C / min, with nitrogen purging rate of 25 mL / min in the sample chamber and 40 mL / min in the balance chamber.
[0184] 4. Dynamic Moisture Adsorption (DVS)
[0185] Instrument: TA Instruments Q5000 SA
[0186] Test method: Place 20-50mg of sample in a pre-peeled sample basket. The sample weight is automatically weighed. Perform DVS test on the sample according to the parameters in Table 7: step time 60min, equilibration time for each RH% 1 hour, total airflow velocity 200sccm, gradient mode test, humidity change 0%–90%–0%, humidity change of 10% for each gradient within the range of 0% to 90%, gradient endpoint is determined by dm / dt method, with dm / dt less than 0.01% and maintained for 10 minutes as the gradient endpoint.
[0187] 5. Nuclear magnetic resonance spectrometer (1H-NMR)
[0188] 5.1 Study on the free alkali crystal form
[0189] Detection method: 1H-NMR spectra were obtained using a Bruker Ascend 500 or WNMR-I 400 NMR spectrometer. Full-frequency excitation was performed with a single pulse of 30 ppm spectral width, 16 scans at a 30° angle, digital orthogonal detection, temperature control at 298 K, and chloroform as the deuterium band reagent.
[0190] 5.2 Salt formation test
[0191] Detection method: 1H-NMR spectra were obtained using a Bruker 400MHz NMR instrument. DMSO-d6 was used as the solvent, full-frequency excitation was performed, with a single pulse of 30ppm spectral width, four 30° angle excitation scans, digital orthogonal detection, and temperature control at 295K.
[0192] 6. Solubility Test
[0193] At room temperature, weigh a known amount of sample, add solvent to the sample in portions, and stir or sonicate to aid dissolution until the sample is visually dissolved. Record the amount of solvent consumed. If the sample is still not dissolved at a specific concentration, its solubility is expressed as "<" the specific concentration.
[0194] 7. Preparation method of biological media
[0195]
[0196] Preparation of Compound A in Example 1
[0197] Prepared according to the method described in Example 2 of WO2021139817A1. The specific method is as follows:
[0198]
[0199] Compound 1S-a (500 mg, 1.84 mmol), N-methylpiperidinone (2S-a, 416 mg, 3.68 mmol), and 2 drops of acetic acid were added to methanol (15 mL) and stirred at room temperature for 1 hour. Sodium cyanoborohydride (231 mg, 3.68 mmol) was then added, and the reaction mixture was stirred overnight at room temperature. The reaction was monitored by TLC until completion. Methanol was removed from the reaction mixture under reduced pressure, followed by the addition of water (10 mL) and extraction with dichloromethane (3 × 20 mL). The combined organic phases were washed with saturated brine, dried over anhydrous sodium sulfate, filtered, and the filtrate was concentrated under reduced pressure. The crude product was purified by silica gel column chromatography (dichloromethane:methanol = 30:1) to give a yellow solid compound 2S-b (500 mg), which was directly used in the next reaction.
[0200] Compound 2S-b (500 mg, 1.50 mmol) and palladium on carbon catalyst (10%, 70 mg) were added to methanol (15 mL) at room temperature. The reaction mixture was stirred for 3 hours at room temperature and under a hydrogen atmosphere at 1 atm. The reaction was monitored by TLC until completion. The reaction mixture was filtered through diatomaceous earth, and the filtrate was concentrated under reduced pressure to obtain a crude product. The crude product was purified by silica gel column chromatography (dichloromethane:methanol = 20:1) to give a brown solid compound 2S-c (280 mg, yield 62%).
[0201] Compound 2S-c (280 mg, 0.93 mmol) and Ib (310 mg, 0.93 mmol) were dissolved in toluene (8 mL). The reaction mixture was stirred at 90 °C for 3 hours. The reaction was monitored by TLC until completion. After the reaction solution was cooled to room temperature, it was concentrated under reduced pressure. The crude product was purified by silica gel column chromatography (dichloromethane:methanol = 20:1) to give a yellow solid compound 2S (180 mg, yield 34%).
[0202] 1H NMR(500MHz,DMSO-d6)δ9.86(bs,1H),8.90(s,1H),7.16(d,J=2.1Hz,1H),7.06(d,J=8.9Hz,1H), 6.81(d,J=8.9Hz,1H),5.91-5.70(m,1H),4.23(dd,J=10.5,2.4Hz,1H),3.89(dd,J=10.5,9.0Hz,1 H),3.69(d,J=11.3Hz,1H),3.00–2.88(m,3H),2.79(d,J=11.2Hz,2H),2.59–2.53(m,1H),2.41(s, 3H),2.34–2.16(m,7H),2.14(s,3H),1.94–1.73(m,9H),1.62-1.51(m,2H),1.48–1.36(m,2H)ppm. MS m / z 572.8[M+H] + .
[0203] The compound 2S is the same as compound A described in this application. Testing revealed that the aforementioned yellow solid compound is amorphous.
[0204] Example 1: Preparation of free base crystal form A-Ⅰ of compound A
[0205] Take about 5 g of the sample obtained in Preparation Example 1, add 100 mL of n-butanol and 10 mL of anisole, heat to 105±5℃, and stir to dissolve. Cool to 85±5℃ to crystallize for 1.5±0.5 h, and continue cooling to 15±5℃ to crystallize for 2.0±0.5 h. Filter, wash with 10 mL of n-butanol, wash with 10 mL of n-heptane, and dry the filter cake under vacuum at 60±5℃ for 4±2 h to obtain the final product.
[0206] The solid was subjected to XRPD characterization, and this crystalline solid was denoted as crystal form Al. The XRPD characterization is as follows: Figure 1-1 As shown, the characterization data are presented in Table 11. The TGA results are shown (see...). Figure 1-2 The crystal form showed a weight loss of 0.30% at -150°C, indicating it is an anhydrous; its decomposition temperature is approximately 342°C. (See DSC spectrum). Figure 1-3 The melting point is approximately 256°C. DVS test results show that the weight change of this crystal form is approximately 0.17% within the 0%RH-90%RH range, and it is non-hygroscopic.
[0207] Table 11 X-ray powder diffraction pattern data of crystalline form AI
[0208] 1 5.24 16.8382 62.6 6301 2 9.62 9.1897 12.5 1253 3 10.44 8.4701 11.7 1177 4 11.46 7.7134 27.1 2729 5 12.89 6.8645 14.1 1420 6 14.19 6.2382 10 1002 7 15.77 5.615 39.1 3938 8 16.36 5.4139 34.1 3427 9 18.69 4.7447 14.6 1471 10 20.28 4.3748 100 10061 11 20.63 4.3024 91.3 9184 12 22.07 4.0241 47.2 4744 13 25.89 3.439 25.6 2577
[0209] The inventors have conducted a systematic study on the preparation method of free alkali crystal form A-Ⅰ. Other exemplary preparation methods include:
[0210]
[0211]
[0212] Example 2: Preparation of the free basal crystal form A-II of compound A (trifluoroethanol solvate of compound A)
[0213] Take about 20 mg of the sample obtained in Preparation Example 1, add 1.0 mL of trifluoroethanol and 0.5 mL of tetrahydrofuran to dissolve it, and dry it rapidly by rotary drying at room temperature to obtain the final product.
[0214] Sampling characterization of XRPD (see) Figure 2-1 Characterization data are shown in Table 12. The obtained crystalline solid is designated as free alkali crystal form A-II. TGA results (see Table 12). Figure 2-2 The crystal form showed a 16.9% weight loss before 150℃ and a decomposition temperature of 343℃, suggesting that this crystal form is a trifluoroethanol solvate of compound A (containing one trifluoroethanol monomer, theoretically accounting for 14.9%). DSC spectrum ( Figure 2-3 The data shows that this crystal form has a desolvation peak at 100℃-130℃ and a melting point of about 256℃ (melting point of crystal form AI).
[0215] Table 12 X-ray powder diffraction pattern data of crystal form A-II
[0216] 1 4.08 21.6154 100 5894 2 16.17 5.4771 37.8 2230 3 16.79 5.2746 21.4 1262 4 17.65 5.0196 5.2 305 5 20.13 4.4072 47 2773 6 20.68 4.2909 70.9 4176
[0217] Example 3: Preparation of the free basal crystal form A-Ⅲ of compound A (dimethyl sulfoxide solvate of compound A)
[0218] Take about 30 mg of the sample obtained in Preparation Example 1, add 5.0 mL of dimethyl sulfoxide, dissolve at 70 °C, stir at room temperature for 2 h to precipitate solid, centrifuge, and vacuum dry at 40 °C overnight to obtain the final product.
[0219] Sampling characterization of XRPD (see) Figure 3-1 Characterization data are shown in Table 13, and the obtained crystalline solid is designated as crystal form A-III. TGA test ( Figure 3-2 The results showed that this crystal form lost 12.4% of its weight before 150℃ and had a decomposition temperature of 342℃, suggesting that crystal form A-III is a dimethyl sulfoxide solvate of compound A (containing one dimethyl sulfoxide, theoretically accounting for 12.0%). DSC studies showed ( Figure 3-3 This crystal form has a desolvation peak at 100℃-150℃ and a melting point of about 256℃ (melting point of free alkali crystal form Al).
[0220] Table 13 X-ray powder diffraction pattern data of crystal form A-III
[0221]
[0222]
[0223] Example 4 Compound A Free Base Crystal Form A-Ⅳ
[0224] Take an appropriate amount of amorphous sample, heat it to 160℃ on a hot stage, hold it at that temperature for 5 minutes, and then let it cool back to room temperature to obtain the sample.
[0225] Sampling characterization of XRPD (see) Figure 4-1 Characterization data are shown in Table 14. The obtained crystalline solid is crystal form A-Ⅳ. TGA spectrum ( Figure 4-2 The data shows that this crystal form loses 0.8% weight before 150℃, and its decomposition temperature is 348℃. (DSC spectrum) Figure 4-3 The data shows that the melting point is approximately 255°C.
[0226] Table 14 X-ray powder diffraction pattern data of crystal forms A-IV
[0227] 1 4.1 21.5074 11.4 2139 2 5.36 16.4669 43.4 8143 3 9.52 9.2846 20.4 3825 4 12.08 7.3229 20.1 3775 5 15.9 5.5685 40.7 7635 6 17.8 4.9783 19.3 3621 7 19.26 4.6055 8.4 1580 8 19.87 4.4655 17.8 3334 9 20.44 4.3424 100 18761 10 20.72 4.2828 89.1 16725
[0228] Example 5 Compound A hydrochloride monohydrate
[0229] Approximately 350 mg of compound A was weighed into a reaction flask, and 7 mL of methanol was added. The mixture was stirred at room temperature to obtain a suspension. After adding 1.05 eq. 1 M hydrochloric acid aqueous solution, the reaction solution remained a suspension, and stirring was continued overnight. The resulting solid was filtered and dried under vacuum at 50 °C for 6 hours to obtain the product (yield 75%, product purity 99.31%).
[0230] IC analysis of the product (Table 15) showed that the molar ratio of free base to hydrochloric acid in compound A was 1:1 (the theoretical chloride ion content in the hydrochloride was 5.8%). Therefore, the crystalline form of compound A hydrochloride (denoted as crystal form B) was successfully prepared in this experiment.
[0231] Table 15 IC results for compound A hydrochloride crystal form B
[0232]
[0233] PLM and XRPD results ( Figure 5-1 The sample was found to be a highly crystalline, irregularly shaped crystal with small particles and some agglomeration, but exhibiting high crystallinity. Characterization data are shown in Table 16 below. TGA showed approximately 4.4% weight loss in the range of room temperature to 130°C. DSC showed two endothermic peaks at 27°C and 253°C, representing the desolvation and melting / decomposition peaks, respectively (see Table 16). Figure 5-2 NMR did not detect any significant organic solvent residue. Therefore, the weight loss was due to water loss, and the hydrochloride crystal is a hydrate (the theoretical water content of a monohydrate is 2.9%), defined as hydrochloride of compound A in crystal form B.
[0234] Table 16 X-ray powder diffraction pattern data of crystal form B
[0235]
[0236] DVS testing was performed on hydrochloride crystal form B. The results showed that the DVS curve of the sample was reversible, and the water content changed with the humidity. The moisture absorption of the sample was 2.4%-5.0% in the range of 10%-90% RH. Furthermore, the XRPD pattern of the sample did not change after the DVS test.
[0237] Different acid equivalents were used to prepare hydrochloride in different solvent systems, as shown in Table 17. Except for the acetone / water (4 / 1) system, which contained some free alkaline crystalline form Al, all other experiments yielded the same XRPD pattern (e.g., Figure 5-1 (as shown); among them, the XRPD spectra of the samples obtained by feeding with 2.1eq. and 5eq. hydrochloric acid are consistent with those of the samples obtained by feeding with 1eq. acid, but the crystallinity of the sample obtained by feeding with 5eq. is slightly worse, and some impurity peaks are detected in the NMR spectrum.
[0238] Therefore, compound A, a free base, undergoes a salt formation reaction with hydrochloric acid in a 1:1 ratio in methanol, acetone, and acetone / water systems; and based on the results of 5 eq. of acid feeding, increasing the proportion of acid did not yield hydrochloride salts in other proportions, and there is a risk of degradation.
[0239] Table 17. Hydrochloride samples prepared under different conditions
[0240]
[0241]
[0242] Example 6 Compound A benzenesulfonate
[0243] The preparation of benzenesulfonate crystal form C using methanol as solvent is described in the following experimental procedure and characterization results.
[0244] Approximately 300 mg of compound A was weighed into a reaction flask, and 6 mL (20°C) of methanol was added. The mixture was stirred at room temperature to obtain a suspension. 1.05 eq. of benzenesulfonic acid solid was added, and the reaction solution immediately became clear. After stirring for 1 hour, no solid precipitated. 30 mL of ethyl acetate was added, and the mixture was stirred overnight at room temperature, after which a solid precipitated. The obtained solid was filtered and dried under vacuum at 50°C for 6 hours to obtain the product (yield approximately 56%, product purity 98.79%).
[0245] PLM and XRPD ( Figure 6-1 The XRPD data shows that the sample is an irregular crystal with small particles and agglomeration. The XRPD characterization data is shown in Table 18 below. Figure 6-2The TGA test showed a weight loss of approximately 0.4% in the range of room temperature to 100°C, which is due to solvent loss. DSC showed an endothermic peak at 235°C, indicating a melting peak. NMR showed that the molar ratio of free base to benzenesulfonic acid in the sample was 1:1. Therefore, compound A benzenesulfonate crystal form C is an amorphous form.
[0246] Table 18 X-ray powder diffraction pattern data of crystal form C
[0247]
[0248] DVS test results show that the sample's moisture absorption is only 1.2% at 80% RH, but within the 80%-90% RH range, the moisture absorption rapidly increases from 1.2% to 7%. Furthermore, during desorption, moisture begins to be removed again at 60% RH, and is essentially removed by 40% RH. Therefore, under high humidity conditions, benzenesulfonate exists in a hydrated crystal form, and crystal form C may transform into a hydrate; however, it can revert to the amorphous form during desorption. Additionally, DVS data shows that the hydrate formed from benzenesulfonate crystal form C undergoes dehydration below 60% RH; it is completely dehydrated at 40% RH, transforming into the amorphous benzenesulfonate form. Therefore, the stable humidity range for this hydrate is 60-90% RH, and it cannot exist stably under low ambient humidity conditions.
[0249] Example 7 Compound A p-Toluenesulfonate
[0250] Methanol and acetone / water were selected as two solvent systems, and p-toluenesulfonate was prepared by adding p-toluenesulfonic acid at a rate of 1 eq. Specific experimental information and results are shown in Table 19.
[0251] According to the characterization results, the ratio of p-toluenesulfonic acid to free base in the product obtained by 1eq. acid feeding was 1:1, and two types of p-toluenesulfonate were obtained: (1) Sample 1 (compound A p-toluenesulfonate crystal form D-Ⅰ) obtained in methanol was a monohydrate (XRPD characterization data can be found in...). Figure 7-1 Characterization data are shown in Table 20 below; (2) Sample 2 obtained in acetone / water (19 / 1) is a mixed crystal of compound A p-toluenesulfonate, a new crystal form (crystal form D-II), and free base (XRPD characterization data are shown in Table 20 below). Figure 8-1 ).
[0252] Table 19 Preparation of Compound A p-Toluenesulfonate
[0253]
[0254] Table 20 X-ray powder diffraction pattern data of crystal form D-I
[0255] 1 7.866 11.23064 20.60% 91.6201 2 9.126 9.68308 100.00% 444.817 3 12.982 6.81386 26.70% 118.829 4 13.299 6.65222 33.00% 146.949 5 15.817 5.59837 29.10% 129.254 6 18.538 4.78238 34.60% 153.973 7 19.565 4.53356 35.30% 156.845 8 20.942 4.23847 87.80% 390.735
[0256] Compound A, p-toluenesulfonate, has low crystallinity (D-I), exhibiting irregular crystals with small particle size. Thermal analysis results are as follows: Figure 7-2 As shown, the TGA spectrum exhibits approximately 4.2% weight loss in the range of room temperature to 150℃. The DSC spectrum shows two broad endothermic peaks at 49℃ and 167℃; the former is due to solvent loss, while the latter may be a melting peak. NMR indicates no residual organic solvent in the sample, and the molar ratio of free base to p-toluenesulfonic acid is 1:1. In conclusion, compound A, p-toluenesulfonic acid crystal form D-I, is a monohydrate (theoretical water content of the monohydrate is 2.3%).
[0257] Characterization results of compound A for toluenesulfonate sample 2 showed that the sample had high crystallinity and consisted of irregular crystals; however, the XRPD spectrum ( Figure 8-1 The sample showed a small amount of free alkali, which was a mixed crystal of crystal form D-II and free alkali. Characterization data are shown in Table 21 below. The TGA spectrum showed a weight loss of approximately 3.8% in the range of room temperature to 130℃, which should be caused by solvent loss. The DSC spectrum showed three endothermic peaks at 70℃, 145℃, and 160℃, which were caused by solvent removal and melting, respectively. Figure 8-2 NMR results showed that the sample contained approximately 0.1% acetone solvent residue, and the ratio of free base to acid was 1:0.9. In summary, compound A, p-toluenesulfonate crystal form D-II, should be a monohydrate. However, due to the presence of a small amount of free base in the sample, characterization data for pure crystal form D-II could not be obtained.
[0258] Table 21 X-ray powder diffraction pattern data of crystal form D-II
[0259]
[0260]
[0261] Example 8 Compound A fumarate
[0262] Compound A obtained in Preparation Example 1 was dissolved in 20V methanol. After adding 1 eq. of fumaric acid, a suspension was formed. 12V methanol solution was added, and the mixture was heated to 50°C and stirred for 3 hours, still forming a suspension. The mixture was then cooled to room temperature and stirred overnight. After filtration, it was dried at 50°C for 20 hours to obtain the crystalline solid. This crystalline solid was defined as crystal form E.
[0263] Compound A, fumarate, has an irregular crystal form E with low crystallinity. XRPD characterization is shown in [reference needed]. Figure 9-1 The characterization data are shown in Table 22 below. The thermal analysis results are as follows: Figure 9-2As shown, the TGA spectrum shows a weight loss of approximately 3.8% in the range of room temperature to 150℃; the DSC spectrum reveals multiple thermal events, including a solvent removal peak at 32℃, an exothermic crystallization peak at 159℃, and endothermic peaks at 222℃, 230℃, and 240℃, which are likely due to melting or decomposition. NMR detected no residual organic solvent in the sample, and the ratio of fumaric acid to free base was 1:1. Therefore, fumarate crystal form E is a monohydrate (theoretically containing 2.5% water), but its crystallinity is low, and it undergoes dehydration even at relatively low temperatures.
[0264] Table 22 X-ray powder diffraction pattern data of crystal form E
[0265] 1 4.148 21.28427 100.00% 1093.55 2 8.35 10.58036 9.20% 100.783 3 12.474 7.09007 14.70% 161.147 4 13.196 6.7039 20.30% 221.679 5 13.917 6.35829 7.20% 78.8464 6 16.608 5.33359 26.30% 287.579 7 19.92 4.45356 34.30% 374.764 8 21.488 4.13208 20.10% 219.281 9 22.113 4.0167 19.30% 211.278
[0266] Example 9 Compound A citrate
[0267] Compound A obtained in Preparation Example 1 was dissolved in 20V methanol, and 1 eq. of citric acid was added to obtain a suspension. After adding 12V methanol solution, the suspension was stirred at 50℃ for 3 hours and remained a suspension. The suspension was cooled to room temperature and stirred at room temperature overnight. After filtration, the suspension was dried at 50℃ for 20 hours to obtain Sample 1.
[0268] Compound A obtained from Preparation Example 1 was dissolved in 20V acetone / water (4 / 1) and heated to 50°C. After adding 2 eq. citric acid, a clear solution was obtained. After stirring for 1.5 hours, no solid precipitated. After cooling to room temperature and stirring at room temperature overnight, a solid precipitated. The solution was filtered and dried at 50°C for 6 hours to obtain Sample 2.
[0269] Characterized by XPRD (see) Figure 10-1 Samples 1 and 2 above belong to the same crystal form—crystal form F. Characterization data are shown in Table 23 below. This crystal form is an irregularly shaped crystal with high crystallinity. Thermal analysis results are as follows... Figure 10-2 As shown, the TGA spectrum indicates a weight loss of approximately 1.6% in the range of room temperature to 150°C. The DSC spectrum shows three endothermic peaks at 30°C, 198°C, and 248°C, which are likely due to solvent loss, melting, and sample decomposition, respectively. 1H-NMR results show that the ratio of free base to citric acid in the sample is 1:1. DVS testing results show that crystal form F has a moisture absorption of approximately 3.8% at 80% RH, and the crystal form of the sample did not change before and after DVS. Citrate may be a channel hydrate, and its water content varies with humidity.
[0270] Table 23 X-ray powder diffraction pattern data of crystal form F
[0271]
[0272] Example 10 Compound A Malate
[0273] Take compound A obtained from Preparation Example 1, add 20V methanol, stir to dissolve, add 1 eq. malic acid to obtain a suspension, add 12V methanol, heat to 50℃, stir to obtain a clear liquid, cool to room temperature after 3 hours, stir overnight to precipitate solid, filter, dry at 50℃ for 20 hours to obtain the product.
[0274] The obtained product was characterized by XPRD (see...). Figure 11-1 The malate crystal form G is denoted as G, and its characterization data are shown in Table 24 below. Malate crystal form G exhibits good crystallinity, forming irregular crystals with agglomeration. Thermal analysis results show (see...) Figure 11-2 The TGA spectrum showed a weight loss of approximately 4.2% in the range of room temperature to 120℃. The DSC spectrum showed four endothermic peaks at 57℃, 175℃, 191℃, and 238℃; the former was due to solvent loss, while the latter three were melting and decomposition peaks. NMR showed that the ratio of malic acid to free base in the sample was 1:1, and there was no residual organic solvent. Therefore, the sample is a monohydrate (the theoretical water content of monohydrate is 2.3%).
[0275] Table 24 X-ray powder diffraction pattern data of crystal form G
[0276]
[0277] Example 11 Succinate of Compound A
[0278] Take compound A obtained from Preparation Example 1, add 20V acetone / water (9 / 1), heat to 50°C, add 1 eq. succinic acid, it is still a suspension, but some solids dissolve, stir for 1 hour, cool to room temperature, add 20V ethyl acetate and stir overnight, filter, dry at 50°C for 20 hours to obtain the product.
[0279] The XRPD spectrum contains free base diffraction peaks, and NMR shows that the molar ratio of free base to succinic acid in the sample is 3:2. Furthermore, the DSC spectrum shows a melting peak of the free base. This suggests that the free base and succinic acid did not react completely, or that the succinate is prone to dissociation.
[0280] Example 12 Compound A Other Salts
[0281] This application also attempted reactions of the free base with other acids (sulfuric acid, methanesulfonic acid, tartaric acid, maleic acid, and phosphoric acid). The specific experimental procedures and results are shown in Table 25 below. The results show that the free base of compound A failed to yield crystalline samples when reacting with maleic acid and phosphoric acid; four crystalline samples were obtained when reacting with sulfuric acid, methanesulfonic acid, and tartaric acid; however, the crystallinity of the obtained samples was low, and they were not characterized in detail. Therefore, the free base failed to yield crystalline salts with acceptable crystallinity when reacting with sulfuric acid, methanesulfonic acid, tartaric acid, maleic acid, and phosphoric acid.
[0282] Table 25 Preparation methods of other salts of compound A
[0283]
[0284]
[0285] Experimental Example 1: Free Base Crystal Form Conversion Test of Compound A
[0286] 1. Crystal-free conversion test
[0287] 1) Preparation of initial mixed sample: Take equal amounts of free alkali of compound A, crystal form A-Ⅰ and crystal form A-Ⅳ, mix them evenly, and take samples for XRPD characterization;
[0288] 2) Add 1 mL of the corresponding solvent to the sample to form a suspension, stir at the corresponding temperature, and take a sample for XRPD characterization.
[0289] Table 26. Conversion test of compound A (free base, non-crystalline form)
[0290]
[0291] 2. Competition experiment between anhydrous substance and solvate and solvent activity experiment
[0292] 1) Take equal amounts of mixed samples of different crystal forms of compound A free base, mix them evenly, and take samples for XRPD characterization;
[0293] 2) Add 1 mL of the corresponding solvent to the mixed sample to form a suspension, stir at room temperature, and take a sample for XRPD characterization.
[0294] Table 27 Competition experiments between anhydrous substances and solvates, and solvent activity experiments.
[0295]
[0296] Experiment Example 2 Stability Test
[0297] Appropriate amounts of compound A (free alkali crystal form A-I), compound A (hydrochloride monohydrate crystal form B), and compound A (benzenesulfonate crystal form C) were placed open and stored for 7 days under three conditions: 60℃, 92.5% RH, and 40℃ / 75% RH. Subsequently, the samples were analyzed by HPLC and XRPD after 7 days to determine their chemical and physical stability.
[0298] Test results showed that the free alkali crystal form A-Ⅰ, the hydrochloride monohydrate crystal form B, and the benzenesulfonate crystal form C of compound A were all chemically stable after being placed at 60℃, 92.5%RH, and 40℃ / 75%RH for 7 days, with no obvious degradation observed. XRPD results showed that the crystal forms of the free alkali crystal form A-Ⅰ and the hydrochloride monohydrate crystal form B of compound A remained unchanged after 7 days under all three conditions; however, the benzenesulfonate crystal form C of compound A transformed into a new crystal form after 7 days under high humidity conditions of 92.5%RH, possibly as a hydrate, while its crystal form remained unchanged under the other two conditions.
[0299] In addition, this application also examined the crystal form of compound A after grinding or pulverizing the free alkali crystal form A-Ⅰ, and found that the crystal form of the sample did not change.
[0300] Table 28 Stability Test Results
[0301]
[0302] Experimental Example 3: Comparison of the solubility of compound A (free alkali crystal form A-I), compound A (hydrochloride monohydrate crystal form B), and compound A (benzenesulfonate crystal form C)
[0303] Compound A hydrochloride monohydrate crystal form B, compound A benzenesulfonate crystal form C, and compound A free base crystal form A-Ⅰ were added to water, SGF, FaSSIF, and FeSSIF, respectively, to prepare sample solutions / suspensions at 5 mg / mL. Two samples were prepared in parallel for each medium. All samples were shaken at 200 rpm for 24 h at 37 °C. Suspensions were collected at 0.5 h, 2 h, and 24 h and filtered. The filtrates were analyzed by HPLC and their pH was determined; the filter cake was analyzed by XRPD.
[0304] The results showed that the solubility of the free base and both salts in SGF was greater than 5 mg / mL; the solubility of the free base in water was relatively low, approximately 0.003 mg / mL; while the solubility of both salts in water was relatively high, with benzenesulfonate showing the highest solubility, exceeding 5 mg / mL at 24 h. In FaSSIF and FeSSIF, the solubility of hydrochloride was slightly higher than that of the free base; however, in FaSSIF, due to crystal transformation, the solubility of benzenesulfonate was lower than that of both the free base and hydrochloride within two hours.
[0305] XRPD tests were performed on the filter cake, and the results showed that during the solubility determination, the free alkali and benzenesulfonate became viscous in FeSSIF. Except for benzenesulfonate, which changed to hydrochloride crystal form I after 0.5 hours in FaSSIF medium, the XRPD patterns of the remaining solids did not change.
[0306] In summary, except that the solubility of compound A in its free alkaline crystal form AI is significantly lower than that of the two salts in water, its solubility in the other three biologically relevant media is not much different from that of the two salts.
[0307] Table 29 Comparison of solubility of compound A (free alkali crystal form A-Ⅰ), compound A (hydrochloride monohydrate crystal form B), and compound A (benzenesulfonate crystal form C)
[0308]
[0309]
[0310] Note: *Compound A benzenesulfonate crystal form C experienced filtration through the filter during filtration in FaSSIF solution. The measured data are the HPLC results of the supernatant obtained after centrifugation.
[0311] Experimental Example 4: In vitro inhibition of tumor cell proliferation by compound A (free alkali crystal form A-I)
[0312] 1. Test Methods
[0313] Tumor cell lines were cultured in an incubator at 37°C and 5% CO2. Cells were passaged periodically, and cells in the logarithmic growth phase were seeded onto culture plates. Cells were stained with trypan blue and viable cells were counted. The cell concentration was adjusted to an appropriate level. Cell suspension was added to each well of the culture plate, and cell-free culture medium was added to the blank control wells. The culture plates were incubated overnight in an incubator at 37°C, 5% CO2, and 100% relative humidity. Compound A (free base form AI) was serially diluted with DMSO from the highest concentration to the lowest concentration (starting from 20 μM, 1:3 dilution, 8 concentration gradients, 3 replicates per gradient). The working solution of the compound was added to the cell culture plates; the same final concentration of DMSO was added to the solvent control wells. The plates were then incubated for 4–7 days. Cell viability was measured according to the instructions of the Promega CellTiter-Glo (CTG) luminescent cell viability assay kit (Promega-G7573).
[0314] The inhibition rate (IR) of the detected compound is calculated using the following formula:
[0315] IR(%) = [1 – (RLU) 化合物 –RLU 空白对照 ) / (RLU 溶媒对照 –RLU 空白对照 )]×100%
[0316] The inhibition rates of different concentrations of the compound were calculated in Excel, and then inhibition curves were plotted and relevant parameters, including minimum inhibition rate, maximum inhibition rate, and IC50, were calculated using GraphPad Prism software. 50 The following formula calculates IC. 50 .
[0317] Y = minimum inhibition rate + (maximum inhibition rate - minimum inhibition rate) / (1 + 10^(LogIC)) 50 -X)*HillSlope))
[0318] X: log(concentration)
[0319] Y: Reaction value, negatively correlated with X.
[0320] HillSlope: Slope Factor
[0321] Note: When the maximum inhibition rate is <50%, the result is expressed as IC50. 50 > Maximum initial concentration.
[0322] 2. Test Results
[0323] The results showed that compound A exhibited good inhibitory activity against the seven breast cancer cell lines tested, and its advantages were significantly better than those of the CDK4 / 6 selective inhibitor Palbociclib. Specifically, compound A showed superior inhibitory activity against both the primary Palbociclib-resistant strain MDA-MB-468(Rb-) and the acquired Palbociclib-resistant strain xMCF-7 / Palbo-R. In particular, compound A demonstrated a more significant therapeutic advantage against the primary Palbociclib-resistant strain MDA-MB-468(Rb-), with a maximum inhibition rate exceeding 99%, while Palbociclib's maximum inhibition rate was only 34%. Compound A also showed superior inhibitory activity against HR+ / HER2- breast cancer cells T47D, triple-negative breast cancer cells HCC1187, and MDA-MB-231 compared to Palbociclib, while its inhibitory activity against HR+ / HER2- breast cancer cells MCF-7 was comparable to that of Palbociclib. In the treatment of HR- / HER2+ breast cancer cells MDA-MB-453, although the IC50 value of compound A was approximately twice that of palbociclib, compound A achieved a near 100% maximum inhibitory rate against this cell line, while palbociclib, even with increased dosage, only achieved a maximum inhibitory rate of approximately 74%. Compound A also demonstrated higher maximum inhibitory rates against other breast cancer cell lines. Therefore, compound A is superior to palbociclib in terms of its maximum effect in inhibiting tumor cell proliferation.
[0324] As a direct downstream target of CDK4 / 6, Rb protein is considered a major biomarker for evaluating the sensitivity of CDK4 / 6 inhibitors. Rb protein deficiency (Rb-) indicates tumor insensitivity to CDK4 / 6 inhibitors (primary resistance). Table 31 shows that compound A significantly inhibited Hep3B (Rb-) liver cancer cells, with a maximum inhibition rate exceeding 99%, suggesting that compound A also has a good therapeutic effect on CDK4 / 6 inhibitor-resistant liver cancer.
[0325] Compound A exhibits excellent inhibitory activity against Rb+ colorectal cancer cells COLO205, HT-29, and HCT116; Rb+ liver cancer cells Huh-7 and JHH-7; hematologic malignancies MV-4-11 and MOLM-13; ovarian cancer cells A2780; small cell lung cancer cells NCI-H211; and melanoma SK-MEL-5.
[0326] Table 30 shows the in vitro proliferation inhibition IC50 of compound A on multiple breast cancer cell lines. 50 Value (CTG test)
[0327]
[0328] Table 31 shows the in vitro proliferation inhibition IC50 of compound A on human tumor cells. 50 Value (CTG test)
[0329]
[0330] Experimental Example 5: Effect of particle size of free alkali crystal form A-I of compound A on formulation dissolution
[0331] Compound A, in its free alkali crystal form A-Ⅰ, is a poorly soluble drug. The particle size of the raw material may affect the dissolution and content uniformity of the formulation, therefore, it is necessary to investigate the particle size of the active pharmaceutical ingredient.
[0332] Using the free alkali crystal form A-Ⅰ of compound A as raw material, raw materials with different particle sizes were selected, and conventional excipients such as fillers and disintegrants were added to compress tablets. The effect of raw material particle size on the dissolution of the formulation was investigated, and the results are shown in the table below.
[0333] Table 32 Effect of raw material particle size on formulation dissolution
[0334]
[0335] Note: Except for the particle size of the raw materials, the composition of Formulation-1 and Formulation-2 is exactly the same.
[0336] Stability study of compound A's free alkali crystal form A-Ⅰ in Experimental Example 6
[0337] The factors affecting the stability of the free alkali crystal form A-Ⅰ of compound A were investigated, and accelerated and long-term tests were completed. The test results are shown in the table below.
[0338] (1) Influencing Factors Experiment
[0339] Table 33. Experimental Results of Factors Affecting the Free Alkali Crystal Form AI of Compound A
[0340]
[0341] Note: "N / A" indicates that it was not tested.
[0342] Conclusion: The results of the investigation of influencing factors show that the properties of compound A, crystal form A-Ⅰ, did not change significantly under the above experimental conditions. Under high temperature conditions, there were no significant changes in related substances; under high humidity conditions, there were no significant changes in moisture absorption weight gain, and the related substances remained unchanged compared to 0%. Under illumination conditions (illuminance of 4500 lx ± 500 lx, and the total illuminance of the light source should not be less than 1.2 * 10⁻⁶), the morphology of compound A, crystal form A-Ⅰ, did not change significantly. 6 lux·hr, near-ultraviolet lamp energy not less than 200W·hr / m 2 It is relatively stable, and no obvious degradation impurities were found. This indicates that the crystal form A-Ⅰ of compound A has good stability.
[0343] (2) Accelerated testing
[0344] Packaging: Simulates market packaging (using pharmaceutical-grade low-density polyethylene bags as inner packaging and polyester / aluminum / polyethylene pharmaceutical packaging composite bags as outer packaging).
[0345] Test conditions: 40℃±2℃ / 75%±5%RH
[0346] Table 34 Results of accelerated testing of compound A's free alkali crystal form in Al.
[0347]
[0348] Note: "N / A" indicates that it was not tested.
[0349] (3) Long-term stability test
[0350] Packaging: Simulates market packaging (using pharmaceutical-grade low-density polyethylene bags as inner packaging and polyester / aluminum / polyethylene pharmaceutical packaging composite bags as outer packaging).
[0351] Test conditions: 25℃±2℃ / 60%±5%RH
[0352] Table 35 Results of long-term tests on the free alkali crystal form A-Ⅰ of compound A.
[0353]
[0354] Note: "N / A" indicates that it was not tested.
[0355] Conclusion: After being placed for 6 months under accelerated testing (40℃±2℃ / 75%±5%RH) and 18 months under long-term stability testing (25±2℃ / 60%±5%RH), the properties, loss on drying, related substances, crystal form and content of the sample were basically the same as those at 0 months, and no obvious increasing trend was observed. This shows that the crystal form A-Ⅰ of compound A has good stability.
Claims
1. Compound A in crystalline form, the structure of which is shown in formula (I): (I) in: The crystalline form of compound A is an anhydrous compound, and the crystalline form of compound A is crystal form A-Ⅰ. Using Cu-Kα radiation, the X-ray powder diffraction pattern expressed in 2θ angles has characteristic peaks at 5.2±0.2°, 9.5±0.2°, 11.4±0.2°, 15.7±0.2°, 16.3±0.2°, 20.2±0.2°, and 22.0±0.2°.
2. Compound A in crystalline form as described in claim 1, wherein: The crystal form A-Ⅰ, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray powder diffraction pattern expressed at 2θ angles at 5.2±0.2°, 9.5±0.2°, 10.4±0.2°, 11.4±0.2°, 12.8±0.2°, 14.1±0.2°, 15.7±0.2°, 16.3±0.2°, 18.6±0.2°, 20.2±0.2°, 22.0±0.2°, and 25.8±0.2°.
3. Compound A in crystalline form as described in claim 1, wherein: The X-ray powder diffraction pattern of the crystal form A-Ⅰ using Cu-Kα radiation is basically as shown in Figure 1-1.
4. Compound A in crystalline form as described in any one of claims 1-3, wherein: The DSC spectrum of the aforementioned crystalline AI exhibits an endothermic peak at 256±3℃.
5. Compound A in crystalline form as described in claim 4, wherein: The DSC spectrum of the aforementioned crystal form AI is basically as shown in Figures 1-3.
6. A pharmaceutical composition comprising compound A in crystalline form as described in any one of claims 1-5, and optionally one or more pharmaceutically acceptable excipients.
7. Use of compound A in crystalline form as described in any one of claims 1-5 or the pharmaceutical composition as described in claim 6 in the preparation of an antitumor drug, wherein: The tumors are selected from liver cancer, colorectal cancer, HR+ / HER2- breast cancer, triple-negative breast cancer, HR- / HER2+ breast cancer, ovarian cancer, small cell lung cancer, melanoma, or hematologic malignancy.
8. Use of compound A in crystalline form as described in any one of claims 1-5 or the pharmaceutical composition as described in claim 6 in the preparation of an antitumor drug, wherein: The tumor is selected from drug-resistant tumors; the drug-resistant tumor is selected from breast cancer or liver cancer that is resistant to CDK4 / 6 inhibitors.
9. The use according to claim 8, wherein: The drug-resistant tumors were selected from breast cancer or liver cancer that were resistant to Palbociclib.
10. The use according to claim 9, wherein: The term "palbociclib-resistant breast cancer" refers to breast cancer that has acquired resistance to palbociclib or breast cancer that has primary resistance to palbociclib.
Citation Information
Patent Citations
Polycyclic compound acting as kinase inhibitor
WO2021139817A1